2004
DOI: 10.1007/s00520-003-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer information disclosure in different cultural contexts

Abstract: The relationship between truth telling and culture has been the subject of increasing attention in the literature. The issue of whether, how and how much to tell cancer patients concerning diagnosis is still approached differently depending on country and culture. The majority of physicians tell the truth more often today than in the past, in both developed and developing countries, but most of them prefer to disclose the truth to the next of kin. Nurses in Anglo-Saxon countries are considered to be the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
150
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 67 publications
3
150
0
13
Order By: Relevance
“…In addition, insufficient information on the diagnosis, prognosis and treatment options will increase anxiety and doubt. [31] When terminal stage cancer patients come face to face with death, they exhibit a common medical condition, and treatment options with the potential for toxicity may need to be considered. These treatment options may include standard therapy or experimental approaches, as well as supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insufficient information on the diagnosis, prognosis and treatment options will increase anxiety and doubt. [31] When terminal stage cancer patients come face to face with death, they exhibit a common medical condition, and treatment options with the potential for toxicity may need to be considered. These treatment options may include standard therapy or experimental approaches, as well as supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…A Lebanese study, during the period from 1995 to 2015, revealed an increase in the percentage of physicians who prefers cancer diagnosis disclosure from 47% to 69% 3 . Factors which influence the attitude and practice of truth-telling in the cancer care setting include culture and physician-related factors 4,5 . Furthermore, medical professionals face the fact that patients are different regarding their desire to know or to ignore their cancer diagnosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, some nations still harbor resistance to this practice, and doctors there choose to speak euphemistically about the diagnosis or even the malignant nature of the disease (Mystakidou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%